PENGARUH PENDEKATAN KONTEKSTUAL BERBASIS KECERDASAN VISUAL-SPASIAL TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Ani, A.; Maulana, M.; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2017)
The contextual approach is an approach that links the material taught to the real life situations of the student, with that matter the students can make the connection between the knowledge who he has with the student's daily life. Based on visual-spatial intelligence, in learning process,teacher more choose playing a color. Color games in learning make students not feel bored. The base of visual-spatial intelligence is applied in the contextual component of modeling and inquiry through the learning community. The purpose of this research is to know the influence of visual-spatial based visual contextual approach towards students' mathematical understanding on simple space building materials and their webs. This research was conducted at elementary school in Gegesik, SDN 2 Panunggul with SDN 2 Kedungdalem. Sampling is done using purposive sampling. The result of calculation from data processing obtained by value of correlation coefficient (R) 0,023 = 2,3%